2021
DOI: 10.1002/aqc.3688
|View full text |Cite
|
Sign up to set email alerts
|

Elasmobranch fishing and trade in Sarawak, Malaysia, with implications for management

Abstract: 1. Many shark and ray (elasmobranch) species are threatened with extinction, due to overfishing and commercial trade 2. Sarawak is situated in Malaysian Borneo in the Coral Triangle: a global priority region for elasmobranch conservation. Malaysia is the world's eighth largest elasmobranch fishing nation, and Sarawak is one of Malaysia's largest fishing states, yet there are limited species-specific data on catch and trade of elasmobranchs to support conservation and fisheries management decisions. 3. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…)-are regularly caught as part of fishers' overall livelihood strategies (Simeon et al, 2020). This is representative of other SSFs in Indonesia, and in the Global South more generally (Booth, Chaya, et al, 2021;Gupta et al, 2020;Haque et al, 2021). Using this case study, we show how the results can be used to inform intervention strategies to change bycatch-relevant behaviours, which are fit for the social and economic context in which they are implemented.…”
Section: Introductionmentioning
confidence: 92%
“…)-are regularly caught as part of fishers' overall livelihood strategies (Simeon et al, 2020). This is representative of other SSFs in Indonesia, and in the Global South more generally (Booth, Chaya, et al, 2021;Gupta et al, 2020;Haque et al, 2021). Using this case study, we show how the results can be used to inform intervention strategies to change bycatch-relevant behaviours, which are fit for the social and economic context in which they are implemented.…”
Section: Introductionmentioning
confidence: 92%
“…The authors' search of online news and social media reports yielded 29 confirmed captures from 2014 to 2022 across Malaysia. Adding these to the reports published by [12,34,38,39] brought the total reported captures of giant freshwater whipray in Malaysia to 61 between 2011 and 2022 [10]. Then et al [10] noted that most individuals were captured with bottom trawls and hook and line.…”
Section: Malaysiamentioning
confidence: 99%
“…Pollution and bottom trawls may be particularly significant to this species in Malaysia given its association with clean water and the high number of individuals captured by trawls [10]. Booth et al [39] documented a large market for elasmobranchs in Sarawak, with over 26,500 individuals worth 125,000 USD traded annually.…”
Section: Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…Within the SEA region, Malaysia is one of the top countries with rich biodiversity of elasmobranch species. To date, there are at least 70 species (19 families) of sharks and 91 species (11 families) of batoids that have been reported to occur in Malaysian waters ( Supplementary Materials Table S1 ) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Although new species are continuously discovered, the populations of sharks and batoids have gradually decreased over the past decades [ 18 ].…”
Section: Introductionmentioning
confidence: 99%